Ethnomathematics in Javanese and Sundanese batik: An AI-assisted comparative analysis - Yusuf Adhitya; Edi Supriyadi (Universitas Sarjanawiyata Tamansiswa, 2024)
This research is an ethnographic study using two AI tools (ChatGPT and Gemini AI) to analyze comparatively the different patterns between Javanese and Sundanese batik. The data was obtained from two AI-generated outputs of two prompts focusing on geometric patterns and transformations. The study used a triangulation process by matching and contrasting AI-generated outcomes with previous literature. The findings reveal that: 1) Javanese batik motifs contain more geometric designs, in the other hand, Sundanese batik tends to use more fluid and organic patterns, and 2) the majority of Javanese batik combines both reflection and rotation, whereas Sundanese batik uses translation and reflection. Math properties from both batik designs are inspired by different cultures. Batik patterns from Java represent values such as balance, organization, and class whereas Sundanese batik expresses Sundanese beliefs about respect for nature. It highlights that traditional arts should be integrated into mathematics teaching to better understand and appreciate their role in various cultures.